The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2478/prolas-2020-0053
|View full text |Cite
|
Sign up to set email alerts
|

Mental Disorders Following Covid-19 Infection: A Systematic Review of Acute and Long-Term Psychiatric Manifestations and Associated Brain Changes

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) primarily affects the respiratory tract, but sometimes also other organs, including the central nervous system (CNS). It is not well understood how the virus affects the CNS and how frequently it happens. Our review provides insight into the occurrence of mental disorders in Corona Virus Disease 2019 (COVID-19) patients. We also collected information about the biological basis of the susceptibility of brain cells to SARS-CoV-2 and its implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…In addition to these studies, all the others found in this review analyzed heterogenic populations of patients with COVID-19, from mild to severe. In this context, a recent editorial and a systematic review provided a detailed overview into the spectrum of mental disorders that can occur during the intermediate and long-term phases of COVID-19 in mild-to-critical patients (114,115). The most frequent neurological long-term symptoms in these patients were myalgia, arthralgia, sleeping troubles, and headache (46,50,61,116).…”
Section: Persistent Neurological Symptoms and Olfactory Dysfunctionsmentioning
confidence: 99%
“…In addition to these studies, all the others found in this review analyzed heterogenic populations of patients with COVID-19, from mild to severe. In this context, a recent editorial and a systematic review provided a detailed overview into the spectrum of mental disorders that can occur during the intermediate and long-term phases of COVID-19 in mild-to-critical patients (114,115). The most frequent neurological long-term symptoms in these patients were myalgia, arthralgia, sleeping troubles, and headache (46,50,61,116).…”
Section: Persistent Neurological Symptoms and Olfactory Dysfunctionsmentioning
confidence: 99%